Utilizing American and Korean College Admissions Exams to Assess Adult ESL Students’ College Readiness - Weiss, Adam; Hwang, Sang (Asian Journal of Social Sciences and Management Studies, 2019)
While colleges in the United States often use standardized tests such as the ACT and SAT to measure students’ college readiness, students’ performance on other international assessments could also provide educators with useful data. Korean universities have utilized the English portion of the Korean College Scholastic Ability Test (CSAT) to measure Korean students’ English language proficiency for decades (Kim et al., 2012; Lee and Winke, 2013; Bae and Lee, 2018). As the majority of Korean students are English Language Learners (ELLs) (Lee, 2014) ELL students participating in English as a Second Language Programs in the United States might also benefit from taking the exam. The present study utilized the Korean College Scholastic Ability Test (CSAT), the ACT English Test, and the ACT Reading Test to evaluate ELL students’ college readiness in the areas of English reading comprehension and English writing conventions and style. Researchers administered the exams to international students who had participated in a semester-long, English as a Second Language (ESL) program at a regional university in the Southwestern United States. The study investigated participants’ perceptions of their experiences taking each exam. Results from student surveys indicated that students viewed the CSAT as a beneficial English assessment and would recommend the exam to other ESL students. Students’ performance on the CSAT proved relatively similar to their performance on the ACT reading and English exams. As such, the CSAT could prove a valuable assessment tool for ESL educators in the United States and across the globe.